The Politics of Māori Image and Design - Jahnke, Robert; Jahnke, Huia Tomlins (He Pukenga Korero: a journal of Māori studies, 2003)
Keywords: cultural appropriation; indigenous data sovereignty; intellectual property; mātauranga māori; rangatiratanga; social life and customs; tāngata whenua

Reflections on Indigenous sovereignty - Kukutai, Tahu (Journal of Indigenous Wellbeing, 2019)
Keywords: data; data sovereignty; indigenous data sovereignty

Empowering Equitable Data Use Partnerships and Indigenous Data Sovereignties Amid Pandemic Genomics - Haring, Rodney C.; Blanchard, Jessica W.; Korchmaros, Josephine D.; Lund, Justin R.; Haozous, Emily A.; Raphaelito, Josie; Hudson, Maui; Tsosie, Krystal S. (Frontiers in Public Health, 2021)
The COVID-19 pandemic has inequitably impacted Indigenous communities in the United States. In this emergency state that highlighted existing inadequacies in US government and tribal public health infrastructures, many tribal nations contracted with commercial entities and other organization types to conduct rapid diagnostic and antibody testing, often based on proprietary technologies specific to the novel pathogen. They also partnered with public-private enterprises on clinical trials to further the development of vaccines. Indigenous people contributed biological samples for assessment and, in many cases, broadly consented for indefinite use for future genomics research. A concern is that the need for crisis aid may have placed Indigenous communities in a position to forego critical review of data use agreements by tribal research governances. In effect, tribal nations were placed in the unenviable position of trading short-term public health assistance for long-term, unrestricted access to Indigenous genomes that may disempower future tribal sovereignties over community members' data. Diagnostic testing, specimen collection, and vaccine research is ongoing; thus, our aim is to outline pathways to trust that center current and future equitable relationship-building between tribal entities and public-private interests. These pathways can be utilized to increase Indigenous communities' trust of external partners and share understanding of expectations for and execution of data protections. We discuss how to navigate genomic-based data use agreements in the context of pathogen genomics. While we focus on US tribal nations, Indigenous genomic data sovereignties relate to global Indigenous nations regardless of colonial government recognition.
Keywords: indigenous data sovereignty

First Nations, Maori, American Indians, and Native Hawaiians as Sovereigns: EAP with Indigenous Nations Within Nations - Haring, Rodney C.; Hudson, Māui; Erickson, Louisa; Taualii, Maile; Freeman, Bonnie (Journal of Workplace Behavioral Health, 2015)
Indigenous workforces have existed across the world since the creation of Earth. What has changed is the evolution of multicultural societies, governments, and landscapes that have become part of, or sit parallel to, sovereign Indigenous nations and their workforces. An international response to Employee Assistance Programming (EAP) and workplace health will be shared from various Indigenous groups across the globe. These societies include the Maori of New Zealand, First Nations of Canada, American Indian groups from the U.S. mainland, and Native Hawaiians. Guidelines for EAP practice include the discussion of historical trauma, communication skills, confidentiality, and environmental issues. Theoretical underpinnings for health sovereignty are shared through ancient teachings of Indigenous philosophies and their relationships to contemporary EAP development and utilization.
Keywords: indigenous data sovereignty; native americans

Enacting Kaitiakitanga: Challenges and Complexities in the Governance and Ownership of Rongoa Research Information - Boulton, Amohia; Hudson, Māui; Ahuriri-Driscoll, Annabel; Stewart, Albert (The International Indigenous Policy Journal, 2014)
Explore millions of resources from scholarly journals, books, newspapers, videos and more, on the ProQuest Platform.
Keywords: data; indigenous data sovereignty; kaitiakitanga; rangatiratanga

Indigenous Perspectives and Gene Editing in Aotearoa New Zealand - Hudson, Maui; Mead, Aroha Te Pareake; Chagné, David; Roskruge, Nick; Morrison, Sandy; Wilcox, Phillip L.; Allan, Andrew C. (Frontiers in Bioengineering and Biotechnology, 2019)
Gene editing is arguably the most significant recent addition to the modern biotechnology toolbox, bringing both profoundly challenging and enabling opportunities. From a technical point of view the specificity and relative simplicity of these new tools has broadened the potential applications. However, from an ethical point of view it has re-ignited the debates generated by earlier forms of genetic modification. In New Zealand gene editing is currently considered genetic modification and is subject to approval processes under the Environmental Protection Authority (EPA). This process requires decision makers to take into account Māori perspectives. This article outlines previously articulated Māori perspectives on genetic modification and considers the continuing influence of those cultural and ethical arguments within the new context of gene editing. It also explores the range of ways cultural values might be used to analyse the risks and benefits of gene editing in the Aotearoa New Zealand context. Methods used to obtain these perspectives consisted of (a) review of relevant literature regarding lessons learned from the responses of Maori to genetic modification, (b) interviews of selected ‘key Maori informants’ and (c) surveys of self-selected individuals from groups with interests in either genetics or environmental management. The outcomes of this pilot study identified that while Māori informants were not categorically opposed to new and emerging gene editing technologies a priori, they suggest a dynamic approach to regulation is required where specific uses or types of uses are approved on a case by case basis. This study demonstrates how the cultural cues that Māori referenced in the genetic modification debate continue to be relevant in the context of gene editing but that further work is required to characterize the strength of various positions across the broader community.
Keywords: data; indigenous data sovereignty

Tracing Opuatia: Repatriating and repurposing colonial land data - Kukutai, Tahu; Whitehead, Jesse; Kani, Heeni (New Zealand Geographer, 2022)
Māori land data produced through colonial systems of dispossession lack interoperability, preventing kin-based communities from tracking their land. Our novel approach to repatriate and harmonise historic land data traces the history of the 45,500 acre Opuatia Block allocated to hapū Ngāti Tiipa in 1866, following the confiscation of 1.2 million acres of Waikato land. Ngāti Tiipa resisted Crown and settler pressures for 30 years, but 80% of Opuatia was alienated within a decade. We discuss the devastation of ‘judicial raupatu’ and the implications of this work for hapū data sovereignty and wider international efforts to achieve Indigenous data sovereignty.
Keywords: colonisation; data sovereignty; hapū; indigenous data sovereignty; iwi; māori land data; repatriation

Indigenous data and health: critical research approaches and indigenous data governance - Reid, Papaarangi; Kukutai, Tahu; Cormack, Donna (European Journal of Public Health, 2018)
Background and objectives:‘Race’ and ethnicity data have become increasingly institutionalised within health research about indigenous peoples. While these data are critical to monitoring the differential distribution of risks and benefits in racialised societies, their uncritical and under-theorised use can perpetuate harmful biologically-deterministic and essentialist approaches to indigenous health. Additionally, indigenous rights and interests in data about us are often overlooked, with issues of indigenous data governance unresolved. The workshop objectives are to: Develop skills to critique uncritical use of ‘race’/ethnicity in indigenous health researchProvide examples from Aotearoa/New Zealand of frameworks or principles of indigenous data sovereignty
Keywords: data; health; indigenous data sovereignty